Comparison of the effect of 8 weeks of resistance training with the use of spirulina on the physical indicators of children aged 5 to 7 years with autism spectrum - Sanaz Alamdar; Saeid Rostami (Movimiento Científico)
Introduction: recently, the prevalence of autism spectrum disorders, which is a neurodevelopmental condition, has increased. Autism is the third most common developmental disorder after mental retardation and cerebral palsy. This study compared aimed the effect of 8 weeks of resistance training with the use of spirulina on the physical characteristics of children aged 5 to 7 years with an autism spectrum.